Алтан хадны бичээс: Урьдчилсан судалгаа - Ц. Баттулга, (Acta Mongolica, 2005)
There is an ancient runic inscription at the winter camp named Altan Khad which is located in the northwest 15 km far from Biger soum in Gobi-Altai province. There are 2 rows of superficial runic scripts as well as very many tantra scripts that were written by Mongolian and Tibetan. The inscription consists of 2 parts and it was carved on the smooth large rock which is on the top of the winter camp.